Soil compaction induced by machinery at polo fields in Argentina - Laureda, Daniel Andrés; Botta, Guido Fernando; Tolón Becerra, Alfredo; Rosatto, Héctor Gustavo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2016)
The land leveling is a form of disturbance of the soil that alters its physical properties. In Argentine the leveling of lands is also extended to a different objective: the sport field construction. The movement of soil from one place to another one produces a rupture of the structure with increase of the volume occupied by air. The soil particles are reordered in a different form from the original one. The soil movements often produce a mixture of edafics horizons. This packing effect diminishes the volume occupied by the pores and increases bulk density and soil tension. One of the main problems that are generated by the land leveling is the compaction. When soil is compacted, non-accommodating faces form smaller aggregates pores. During the whole work, different problems appears, such as: leveling precision; project mark errors in the land, the machinery passes calculation to carry out the work; soil moisture content at the land leveling and the rain value during the earth movement. The present study was carried out in fields located 100 km away from Buenos Aires (34º31'47" S 59º02'15" W). The main objectives of the work were i) to contribute with evidence to the now-a-day knowledge platform, related to the soil physical-mechanical behavior in soils subjected to soil movement with sport aims; ii) to feature the mechanical behavior of a typical argiudol soil in a land leveled polo field. The more important results were: a) swelling factor values > 25%, b) the impact of the soil movement on the organic mater content is smaller than the one happened on the physical parameters, c) both, the traffic intensity as well as the machinery weight have influence on the swelling factor index/compaction d) the machinery passes produces subsoil compaction. Top soil compaction is given, in a further degree, in a field in use, due to the uses of maintenance machineries and the horse transit for the game.